Meningkatkan Aktivitas dan Hasil Belajar Menggunakan Kombinasi Model PBL, NHT, dan Mind Mapping Muatan IPA - Noor Halifah Rizqi; Aslamiah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is that students tend to be passive during the learning process which has an impact on the low learning outcomes of students in science subjects due to the lack of student understanding in understanding the concept of science learning. This study aims to analyze the increase in student activity and learning outcomes in science content of animal life cycle material using a combination of PBL, NHT and Mind Mapping models. The research method used is a qualitative approach with the type of class action research. Classroom action research was conducted in three meetings. The subject group in this study were fourth grade students at SDN Benua Anyar 2 Banjarmasin in the 2022/2023 school year, consisting of a total of 24 students. The data collection techniques in this study were descriptive analysis and cross tabulation analysis. The results showed that student activity increased at meeting III by 92% with the criteria that almost all students were active. Likewise, there was an increase in individual student cognitive learning outcomes at meeting III learning reached 92% with the criteria that almost all students were complete. For principals, teachers, and other researchers, the recommendation that can be taken from this research is that the findings can be an option and guide in choosing a learning model that can increase student participation and learning outcomes.